2013
DOI: 10.1249/mss.0b013e31828e18e6
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure of Constant- and Variable-Intensity Cycling

Abstract: Findings support the use of calibrated power meters for estimating cycling EE. For trained female road cyclists, total mechanical work (kJ) multiplied by 5.3 (GE = 19%) provides a valid estimation of total EE during variable-intensity cycling <75% MAP, although determining each athlete's GE improves accuracy greatly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The recommendations note that cycling is often a moderate activity, with estimates that it would require four to seven calories per minute while cycling (Pate et al, 1995). Although many studies are focused on the health benefits of cycling, most tests of the calories spent during cycling are conducted in the lab, which does not have stop signs and other features one would find in the community (e.g., Haakonssen et al, 2013). A study that included both lab and community measures of cycling found that cyclists tend to ride faster in the lab and when they were wearing a measuring mask than when they were keeping diary entries of cycling (De Geus et al, 2007).…”
Section: 0 Introductionmentioning
confidence: 99%
“…The recommendations note that cycling is often a moderate activity, with estimates that it would require four to seven calories per minute while cycling (Pate et al, 1995). Although many studies are focused on the health benefits of cycling, most tests of the calories spent during cycling are conducted in the lab, which does not have stop signs and other features one would find in the community (e.g., Haakonssen et al, 2013). A study that included both lab and community measures of cycling found that cyclists tend to ride faster in the lab and when they were wearing a measuring mask than when they were keeping diary entries of cycling (De Geus et al, 2007).…”
Section: 0 Introductionmentioning
confidence: 99%
“…Various ways to estimate EE in the field have been developed, but each method has its own limitations [1]. Unique to the cycling community, power output and gross efficiency (GE) have been used to estimate EE outside of the laboratory [16,19,25,33]. This has become possible through the use of bicyclemounted power meters which allow power to be accurately and precisely measured in the field [4,14,15,19,20,24].…”
mentioning
confidence: 99%
“…GEs of 20 and 25 % have been used to estimate EE when a laboratory-derived GE is not determined [2,25,33]. However, it is well documented that individual mean GEs derived from graded exercise tests (GXTs) vary across individuals from 17.3 to 22.6 % during typical cycling power outputs [7,16,20,27,28]. Considering this range, utilizing an individual's mean GE will improve the accuracy of estimating EE.…”
mentioning
confidence: 99%
See 2 more Smart Citations